The Stimulatory Effect of Mixtures Milk Thistle and Wild Safflower Oil with some Insecticides on the Adults and Larvae of Flour Beetles: (NTU Journal of Agriculture and Veterinary Science, 2023)
AbstractThe aim of the current study is testing the mortality effect of mixtures of Milk thistle and Carthamus tinctorius oils with some insecticides on the whole and larvae of flour beetles using three different pesticides: Aktara, Indoxacarb and Alfacypermethrin, using the four different concentrations 50, 100, 200, 500 ppm for each mixing ratio (oil: pesticide) in the general rate mortality of the concentrations of oil mixture with pesticides in the adults and larvae of flour beetles. The results of the statistical analysis showed a clear significant difference between the general averages of the mortality ratios of the four concentrations. The results also indicated the values of propensity, LC50, and the total activation ratios of the mixtures of Milk thistle oils and Sob with the pesticides Aktara, Indoxacarb, and Alfacypermethrin. A variation in the LC50 values for the mixtures of oils with pesticides was noticed, but there is an increase in the toxicity of the mixture of oil and Indoxacarb pesticide compared with the mixtures of oil, Aktara pesticide and alfacypermethrin. The LC50 values for mixtures of Milk thistle and Carthamus tinctorius oils with Indoxacarb pesticide reached 34.5 and 17.9 ppm on caterpillars and 46.4 and 23.5 ppm on adults, while it reached 46.4 and 23.5 ppm for mixtures The oils themselves with the Aktara pesticide were 858.5 and 715.3 ppm on caterpillars and 190.3 and 538.7 ppm on adults. As for the mixtures of oils with Alfacypermethrin, they were 3194.4 and 248.5 ppm on caterpillars and 307.8 and 1410.5 ppm on adults.